Pengembangan Guru Sebagai Sumber Daya Manusia Di Era Digital - Nur Lutfiatul Jannah; Ida Rindaningsi (Insan Zenius Ilmiah, 2024)
In the era of digital technology advancement, the rapid development of digital technology has brought significant changes to life, including the world of education. The impact and challenges brought about by digital transformation drive education to undergo significant changes. Amid the rapid advancement of digital technology, teachers are not only required to master the subject matter but also to be able to utilize technology to enhance the learning process and adapt to the changes that occur. The research method used is a literature review on human resource development in the digital era, with various references taken from journal articles on Google Lens and Google Scholar. The findings of this study indicate that the development of teachers as human resources in the digital era is very important to support teachers in enhancing their skills, competencies, and professionalism in teaching. With proper development, teachers can make significant contributions to the improvement of education quality, which will eventually produce high-quality graduates capable of competing in the digital world.